Road Maps of the Transition : The Baltics, the Czech Republic, Hungary, and Russia - Marrese, Michael; Koen, Vincent; Lutz, Mark.; Saavalainen, Tapio (Washington, D.C. : International Monetary Fund, 1995)
Four papers analyze the process of transition to a market economy in the Baltics, the Czech Republic, Hungary, and Russia through early 1995.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet